Pengaruh Perawatan Air Laut dan Air Tawar terhadap Kuat Tekan Beton Geopolymer yang Memadat Sendiri - Nurtanto, Dwi; Rahayu, Adelia Adyb; Wahyuningtyas, Winda Tri (Rekayasa, 2021)
The replacement of 10% cement as pozzolan material with cementitious materials such as fly ash and rice husk ash aims to improve the quality and durability of concrete to aggressive environments, under normal environmental conditions fly ash and rice husk ash are able to improve the quality of concrete. Based on the review was conducted research on the influence of curing sea water and fresh water to strong press self-compacting concrete with fly ash and rice husk ash as a substitute for cement. Cylindrical test objects measuring 10 x 20 cm with strong concrete press testing at the age of 28 and 56 days to determine the durability of concrete to aggressive environments. The process of curing sea water affects the compressive strength as well as the durability of concrete at the age of 28 and 56 days. The highest average compressive strength increases by 19-24% from normal concrete.